Study of novel potassium permanganate staining in comparison with conventional ZN staining for the diagnosis of pulmonary tuberculosis - Banu, A; Anand, T (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
An estimated 1.8 billion individuals are infected worldwide with the Tuberculosis and there is one death due to it every 15 minutes. It is essential that a fast, effective and inexpensive diagnostic test for TB is developed as early diagnosis stands central to the control of the disease. Traditional diagnosis of tuberculosis is still dependent on sputum microscopy by ZN stain that requires expertise and lacks sensitivity. In this study, we tried to evaluate the use of potassium permanganate staining which is easy, inexpensive and does not require much expertise for screening. Potassium permanganate oxidises Mycolic acid present in cell wall of Mycobacterium sp. which evolves an identifiable oxidation pattern. This study was undertaken to investigate this property of potassium permanganate as a typical laboratory test bridging the gap between sensitivity and time restraint required for an early diagnosis of tuberculosis. The sputum samples (early morning – spot) were collected from patients. From each sample two slides were prepared; one was stained with ZN stain and other with modified potassium permanganate staining. Sputum samples were simultaneously cultured on LJ media after decontamination and concentration. The pattern evolved on staining with potassium permanganate was observed under light microscope and assessed as a diagnostic tool. We found that the pattern formed on oxidation was in association with the AFB status of the sputum (p= 0.0001). Keywords: Acid-Fast bacilli; Mycolic acid; Potassium permanganate oxidation. DOI: 10.3126/saarctb.v7i1.3959 SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(1) 22-25